ANALISIS SPASIAL TINGKAT PERAMBAHAN DI KAWASAN HUTAN LINDUNG KECAMATAN DOLO SELATAN KABUPATEN SIGI - Army Mujiani; Akhbar Akhbar; Abdul Wahid (Universitas Tadulako, 2017)
Forest encroachment and both of its complexity and implication is a problem that faced not only an area/region but also all forest areas in the country, so that the encroachment has been a national scale problem that supposed to have serious attention especially to overcome it. Natural disaster such as flood, landslide that always happened in rainy season and often cause hundreds of unguilty victim. The research was to find out the result of interpretation and the width of protected forest encroachment, South Dolo Subdistrict Sigi Dictrict. The research applied supervised classification and NDVI (Normalized Difference Vegetation Index) analysis. The analysis used in the research was managing image digitally that used for image correcting, image band compositing, image cutting, image sharpening and clarifying. Based on the research it was found that the clarification result of land covering consisted of primary forest, secondary forest, opened lang, plantation and settlement. The map of land covering for the research had the accuracy level of 86%, meant that the map for the research fulfilled the standart of carefulness interpretation and very good for seeing the class of land covering type in protected forest of South Dolo Subdistrict Sigi District. The area of Protected Forest in South Dolo Subdistrict had density level with interval vegetation Index (NDVI) from -0,58 to 0.07 with 966,50 width or 100 % percentage. The result of scoring count showed that the result of NDVI with rare criteria was -0,58- 0,07 and the land use that consisted of forest with width of 26.947,79 ha (93,04 %) and encroachment rate of 180 and in the category of fair encroachment level, good managed land in width of 3.92,99 ha (1,35%) encroachment rate 240 with high encroachment level, and bad managed land with widht of 1.625,72ha (5,61 %) and encroachment rate of 300 was in the level of high encroachment, therefore the total width was 28.966,50 ha (100%).Keywords: Encroachment, Protected Forest, NDVI.